Original paperTHE EFFECT OF AEROBIC CONTINUOUS AND INTERVAL TRAINING ON LEFT VENTRICULAR STRUCTURE AND FUNCTION IN MALE NON-ATHLETES - Mahdiabadi, J.; Gaeini, A.A.; Kazemi, T.; Mahdiabadi, M.A. (Biology of Sport, 2013)
Exercise plays an important role to improve cardiovascular performance. The aim of this study was to compare the effect of aerobic continuous and interval training on the left ventricular structure and function. Twenty untrained healthy male students (aged 18-22 years) were randomly divided into two groups: continuous (C; n=10) and interval (I; n=10). The training programme consisted of countryside jogging for 45 min during 8 weeks three times a week at 70% of maximum heart rate (MHR). In each session group C was jogging for 45 min and in group I jogging was performed in 5 nine-minute stages with a four-minute inactive rest between them. M-mode, 2-dimensional, colour and Doppler transthoracic echocardiography were performed, during resting conditions, before and after the training period. After 8-week training the end diastolic diameter, systolic blood pressure and diastolic blood pressure in groups C and I, and the posterior wall thickness and the end systolic diameter in group I showed no significant difference (P>0.05). On the other hand, the percentage of ejection fraction and shortening fraction in groups C and I, the end systolic diameter and the posterior wall thickness in group C and the interventricular septum thickness in group I demonstrated a significant difference (P≤0.05). Comparing the two groups, only the value of the interventricular septum thickness was significant (P≤0.05). In general, eight-week aerobic continuous and interval training can affect left ventricular structure and function.